STATUS HUKUM ANAK LUAR KAWIN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 - Martinelli, Ida (Universitas Muhammadiyah Sumatera Utara, 2016)
Decision of Constitutional Court gives the child outside the civil status married to the biological father, the purpose of which provide legal protection to children outside of mating, so that the child’s rights as a whole can be obtained. The legal relationship between the child outside of mating with her biological father must be proven with science and technology and/or other evidence according to the law have blood relations.